THE EFFECT OF PERCEIVED VALUE, CUSTOMER ENGAGEMENT, AND SOCIAL INFLUENCE ON PURCHASE INTENTION OF VIRTUAL ITEMS IN MOBILE LEGENDS: BANG BANG AMONG GENERATION Z - Tene, Prilly Ferent Claudysa; Tumbuan, Willem J. F. A.; Gunawan, Emilia M. (Universitas Sam Ratulangi, 2024)
Despite its popularity, Mobile Legends has experienced a decline in in-app purchase revenue since 2021, emphasizing the need to understand the factors effecting purchase intentions among players especially Z Generation as the primary target market due to their high engagement with gaming and prone to spending on virtual items. This study aims to know the effect of perceived value, customer engagement, and social influence on purchase intention of virtual items in Mobile Legends among Gen Z. Utilized a quantitative research method through an online questionnaire targeted at Generation Z used purposive sampling method with a sample of respondents 107 Mobile Legends players across Indonesia and were analyzed using multiple linear regression. This study indicated that perceived value, customer engagement, and social influence had a significant positive effect on the purchase intention of virtual items Mobile Legends among Generation Z, both partially and simultaneously. Keyword: Perceived Value, Customer Engagement, Social Influence, Purchase Intention